Transgender women and the Gender Reassignment Process: subjection experiences, suffering and pleasure in body adaptation - Analídia Rodolpho Petry
OBJECTIVE: This article seeks to understand the experiences of transgender women in relation to the hormone therapy and sex reassignment surgery that make up the Gender Reassignment Process. METHOD: It is a qualitative study inserted into the field of cultural and gender studies. Data collection used narrative interviews, conducted in 2010 and 2011, with seven transsexual women who had been undergoing the Gender Reassignment Process for at least two years. The data was submitted to a thematic analysis. RESULTS: The results show that the transformation processes for construction of the female body include behavior adaptation, posture modification, voice modulation, hormone use, vaginal canal dilation and surgical complications. Such processes subject the body to be built as idealized to fit the gender identity, infringing on pleasures and afflictions. CONCLUSION: We concluded that the discussion involving the Gender Reassignment Process brings allowances for nursing regarding body changes experienced by transgender women.